The Recombinant Protein Based on Trypanosoma cruzi P21 Interacts With CXCR4 Receptor and Abrogates the Invasive Phenotype of Human Breast Cancer Cells - Borges, Bruna Cristina; Uehara, Isadora Akemi; dos Santos, Marlus Alves; Martins, Flávia Alves; de Souza, Fernanda Carvalho; Junior, Álvaro Ferreira; da Luz, Felipe Andrés Cordero; da Costa, Mylla Spirandelli; Notário, Ana Flávia Oliveira; Lopes, Daiana Silva; Teixeira, Samuel Cota; Teixeira, Thaise Lara; et al. (Frontiers in Cell and Developmental Biology, 2020)
Trypanosoma cruzi P21 is a protein secreted by the parasite that plays biological roles directly involved in the progression of Chagas disease. The recombinant protein (rP21) demonstrates biological properties, such as binding to CXCR4 receptors in macrophages, chemotactic activity of immune cells, and inhibiting angiogenesis. This study aimed to verify the effects of rP21 interaction with CXCR4 from non-tumoral cells (MCF-10A), and triple-negative breast cancer cells (MDA-MB-231). Our data showed that the MDA-MB-231 cells expressed higher levels of CXCR4 than non-tumor cell lines. Besides, cytotoxicity assays using different concentrations of rP21 showed that recombinant protein was non-toxic and was able to bind to the cell membranes of both cell lineages. In addition, rP21 reduced migration and invasion of MDA-MB-231 cells by downregulation of MMP-9 gene expression. In addition, the treatment with rP21 blocked the cell cycle arresting it in the G1 phase, mainly in MDA-MB-231 cells. Finally, rP21 prevents the chemotactic and proliferative induced by CXCL12. Our data showed that rP21 binds to the CXCR4 receptors in both cells, downregulates CXCR4 gene expression and decreases the receptors in the cytoplasm of MDA-MB-231 cells, suggesting CXCR4 internalization. This internalization may explain the desensitization of the receptors in these cells. Thus, rP21 prevents migration, invasion, and progression in MDA-MB-231 cells.